Myocardial Perfusion in Hypoplastic Left Heart Syndrome. (October 2021) - Rickers, Carsten; Wegner, Philip; Silberbach, Michael; Madriago, Erin; Gabbert, Dominik Daniel; Kheradvar, Arash; Voges, Inga; Scheewe, Jens; Attmann, Tim; Jerosch-Herold, Michael; Kramer, Hans-Heiner
Abstract : Background: The status of the systemic right ventricular coronary microcirculation in hypoplastic left heart syndrome (HLHS) is largely unknown. It is presumed that the systemic right ventricle's coronary microcirculation exhibits unique pathophysiological characteristics of HLHS in Fontan circulation. The present study sought to quantify myocardial blood flow by cardiac magnetic resonance imaging and evaluate the determinants of microvascular coronary dysfunction and myocardial ischemia in HLHS. Methods: One hundred nineteen HLHS patients (median age, 4.80 years) and 34 healthy volunteers (median age, 5.50 years) underwent follow-up cardiac magnetic resonance imaging ≈1.8 years after total cavopulmonary connection. Right ventricle volumes and function, myocardial perfusion, diffuse fibrosis, and late gadolinium enhancement were assessed in 4 anatomic HLHS subtypes. Myocardial blood flow (MBF) was quantified at rest and during adenosine-induced hyperemia. Coronary conductance was estimated from MBF at rest and catheter-based measurements of mean aortic pressure (n=99). Results: Hyperemic MBF in the systemic ventricle was lower in HLHS compared with controls (1.89±0.57 versus 2.70±0.84 mL/g per min; P <0.001), while MBF at rest normalized by the rate-pressure product, was similar (1.25±0.36 versus 1.19±0.33; P =0.446). Independent risk factors for a reduced hyperemic MBF were an HLHS subtype with mitral stenosis and aortic atresia ( P =0.017), late gadolinium enhancement ( P =0.042), right ventricular diastolic dysfunction ( P =0.005), and increasing age at total cavopulmonary connection ( P =0.022). The coronary conductance correlated negatively with systemic blood oxygen saturation (r, −0.29; P =0.02). The frequency of late gadolinium enhancement increased with age at total cavopulmonary connection ( P =0.014). Conclusions: The coronary microcirculation of the systemic ventricle in young HLHS patients shows significant differences compared with controls. These hypothesis-generating findings on HLHS-specific risk factors for microvascular dysfunction suggest a potential benefit from early relief of frank cyanosis by total cavopulmonary connection. Abstract : Supplemental Digital Content is available in the text.